THE INFLUENCE OF WORKING DISCIPLINE, WORKING ENVIRONMENT AND COMPENSATION ON EMPLOYEE SATISFACTION IN THE EAST JAVA RUBBER INDUSTRY - Nikma Yucha; Akhyar Bisri Al Mustofa (Universitas Maarif Hasyim Latif, 2022)
This study aims to determine whether: 1. Work discipline significantly affects job satisfaction at Surabaya East Java, and 2. Does the work environment affect the job satisfaction of Surabaya Rubber Industry employees, 3. Does compensation impact the job satisfaction of Surabaya Rubber production employees? The sampling technique uses observation, interview, and questionnaire methods. Data was obtained by distributing questionnaires related to work discipline, work environment and compensation to respondents. The data analysis technique in this study was a questionnaire with a Linkert scale using the SPSS application. The results of this study indicate that the work discipline variable has a positive and significant effect on PT employees' job satisfaction. Rubber Ngagel Surabaya Wira East Java. Work environment variables have a positive and significant impact on employee job satisfaction.